2021
DOI: 10.1073/pnas.2102244118
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized detonation for hypersonic propulsion

Abstract: Future terrestrial and interplanetary travel will require high-speed flight and reentry in planetary atmospheres by way of robust, controllable means. This, in large part, hinges on having reliable propulsion systems for hypersonic and supersonic flight. Given the availability of fuels as propellants, we likely will rely on some form of chemical or nuclear propulsion, which means using various forms of exothermic reactions and therefore combustion waves. Such waves may be deflagrations, which are subsonic reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Based on the unique characteristics of radiation signals, a determination method of PDE fill fraction is proposed, i.e., the time spent in the detonation products exhausting process can be obtained according to the characteristics of radiation signals in each process, and then the filling condition of fuel in detonation tube can be calculated. (2) In this experimental study, the detonation and deflagration are found through pressure measurement. The radiation signals of detonation and deflagration are significantly different, and the radiation signal generated by detonation wave is much larger than that of the deflagration wave.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the unique characteristics of radiation signals, a determination method of PDE fill fraction is proposed, i.e., the time spent in the detonation products exhausting process can be obtained according to the characteristics of radiation signals in each process, and then the filling condition of fuel in detonation tube can be calculated. (2) In this experimental study, the detonation and deflagration are found through pressure measurement. The radiation signals of detonation and deflagration are significantly different, and the radiation signal generated by detonation wave is much larger than that of the deflagration wave.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the traditional pressure sensor test method, the spectral radiation method has obvious advantages in identifying the combustion mode: (1) By analyzing the visible radiation signal in the detonation process, the online monitoring of the performance of the detonation engine can be realized by obtaining the working state as well as the fill fraction of the detonation engine at the same time, while the traditional method can only realize the simultaneous measurements by using many more sensors. (2) The spectral radiation test is non-contact, which can avoid the problems of inconvenient installation of conventional contact test methods and sensibility to the environment temperature.…”
Section: Detonation and Deflagrationmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists of a precursor shock travelling at supersonic speed and a reaction zone immediately behind the shock. Applications can be found in areas such as detonation engines [2,3] and plasma-detonation deposition [4]. On the other hand, uncontrolled detonation may damage equipment and cause injury [5].…”
Section: Introductionmentioning
confidence: 99%
“…The oblique shock compresses the fuel-air mixture, and at appropriate compression (combination of θ with θ CJ < θ < θ detach and M ∞ ), the oblique shock will transit into an oblique detonation wave through two mechanisms: abrupt transition and smooth transition [7]. The abrupt transition consists of oblique shock with a non-reactive initiation zone, deflagration wave and an oblique detonation wave forming a triple point [4,8,9]. In contrast, a smooth transition occurs with a curved shock at high Mach numbers with a requirement of a low activation energy condition.…”
Section: Introductionmentioning
confidence: 99%